Cinema, maternidade e luto: analisando o horror em O Babadook (2014) e Hereditário (2018) - Dantas, Clara Letícia de Araújo (2023)
The present master’s thesis consists of a research about the representation of motherhood in cinema, specifically observing horror films. We rely on theoretical concepts of Communication and Psychoanalysis; and we use the Film Analysis method to examine the mothers of the films The Babadook (2014) and Hereditary (2018) – understanding their participation in the respective plots and their relationship with grief, picking up correspondences, comparing the data obtained, as well as identifying similarities and divergences in their narratives, in order to comprehend how the titles in question interact with each other and within the modern horror genre.